2016
DOI: 10.2298/vsp140114145j
|View full text |Cite
|
Sign up to set email alerts
|

Experience of the air medical evacuation team of Serbian armed forces in the united nations mission in the Democratic Republic of Congo - deployment stress and psychological adaptation

Abstract: This analysis indicates that out of all the observed factors, the most important is appropriate selection of personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Joint efforts and positive interactions among team members created higher quality teams. This led to companies gaining competitive advantages in the marketplace and improving organizational performances (Jokovi , Kristic, Stojanovi , & Špiri , 2016;Savage, 2012;Tabassi, Ramli, Roufechaei, & Tabasi, 2014;Warrick, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Joint efforts and positive interactions among team members created higher quality teams. This led to companies gaining competitive advantages in the marketplace and improving organizational performances (Jokovi , Kristic, Stojanovi , & Špiri , 2016;Savage, 2012;Tabassi, Ramli, Roufechaei, & Tabasi, 2014;Warrick, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other programmatic initiatives such as counseling and peer support models have also been shown to be helpful (Curling & Simmons, 2010). Studies have identified having someone to talk to, and training regarding the emotional distress that is common in aid work, as essential to protecting staff against severe emotional distress and burnout (Jokovic et al, 2016). Trauma-specific training has been found to decrease the potential for vicarious trauma (Harr, 2013).…”
Section: Adapting To Stressmentioning
confidence: 99%